2022
DOI: 10.1039/d2ta03269d
|View full text |Cite
|
Sign up to set email alerts
|

Oriented design of triple atom catalysts for electrocatalytic nitrogen reduction with the genetic-algorithm-based global optimization method driven by first principles calculations

Abstract: To rationally locate the high-performance atomically dispersed catalyst remains a challenge, albeit wide explorations in numerous critical chemical reactions. Here, taking the cohesive-energy property of metal (Ec) as the descriptor,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…To study the synergistic effect between three nuclear metal atoms, Wang et al systematically simulated the catalytic performance of single atoms, dual atoms and triple atoms in the electrocatalytic NRR by theoretical calculations. 144 The results showed that the catalytic activity of the TAC was generally superior to that of the SAC and DAC since the reduction of adsorption energy of the NH 2 intermediate effectively promotes the rate control step of *NH 2 hydrogenation. Due to the relatively low loading capacity of single/double/triple site catalysts, there are few active sites which affect the catalytic activity.…”
Section: Reasonable Control Of the Geometric And Electronic Structure...mentioning
confidence: 98%
“…To study the synergistic effect between three nuclear metal atoms, Wang et al systematically simulated the catalytic performance of single atoms, dual atoms and triple atoms in the electrocatalytic NRR by theoretical calculations. 144 The results showed that the catalytic activity of the TAC was generally superior to that of the SAC and DAC since the reduction of adsorption energy of the NH 2 intermediate effectively promotes the rate control step of *NH 2 hydrogenation. Due to the relatively low loading capacity of single/double/triple site catalysts, there are few active sites which affect the catalytic activity.…”
Section: Reasonable Control Of the Geometric And Electronic Structure...mentioning
confidence: 98%
“…Confining multiple Fe and Cu atoms in the surface cavities in graphitic carbon nitride can capture N 2 molecules/intermediates with optimized strength, significantly increasing the ammonia yield and the Faradaic efficiency of NRR [35]. There are also theoretical works on triatomic cluster catalysts for understanding the underlying intrinsic factors and screening candidates for efficient NRR [36][37][38][39][40]. These works demonstrate that the size of the metal particles reduced to the ultra-small cluster obviously changes the electronic properties of catalysts, so the number and type of metal atoms play a key role in the enhancement of the electron transfer process, which will further influence the catalytic performance.…”
Section: Introductionmentioning
confidence: 99%